Regularities in the behavior of the line profiles in neon emission spectra in an alternating electric field - Koryukina, Elena V. (Russian physics journal)
A computer simulation of the spectral line profiles of the neon atom in an alternating circularly polarized electric field is carried out. Calculations are performed within the framework of the unified theoretical approach based on numerical solution of the non-stationary Schrodinger equation. Simulation results make it possible to establish a number of regularities in the behavior of the neon spectral line profiles under changes in the electric field parameters; the dependences of the line profiles on the electron density of plasma and on the temperature of neon atoms are also considered.